TRAINING AND MENTORING ALTERNATIVE FEED FORMULATIONS FOR DUMBO CATFISH (CLARIAS SP.) IN TAWANGARGO VILLAGE, MALANG DISTRICT - Islamy, R Adharyan (Caring: Jurnal Pengabdian Masyarakat, 2024)
The development of the fisheries sector has a significant contribution in improving the economy, especially in Indonesia, which has great potential but has not been utilized optimally. In Tawangargo Village, Malang Regency, training and assistance was carried out for alternative feed formulations for Dumbo catfish (Clarias sp.). This activity aims to empower the community by increasing skills and knowledge in cultivating freshwater fish. The methods used include a community approach, outreach through seminars and direct practice, as well as assistance in alternative feed formulation. The activity stages include initial surveys, outreach and training, which were responded positively by the local community and youth. The cultivation medium is made from a mixture of chicken and cow manure, EM4, molasses and fermented water, then dried in the sun and sprayed with EM4 again before use. Fermented feed is made from cow dung, tofu dregs, corn and rice bran, pellets, EM4, molasses, tape yeast, vitamin C, and water which is fermented for 7 days. The results of the activity show that catfish farming business actors in Tawangargo Village can formulate alternative feed with low costs, easy methods, and efficient results, thereby reducing losses. This training also increases the community's knowledge and ability to make maximum use of land for cultivating freshwater fish, supporting the sustainability of the local economy